Integrating Gamification in Christian Religious Education: A Reflection-Based Theological Model - Nella Mariana Panjaitan (Indonesian Journal of Christian Education and Theology, 2026)
This study aims to analyze the implementation of gamification in Christian Religious Education (CRE) and to propose a learning model that preserves spiritual values. The rapid development of digital technology has encouraged the adoption of more interactive learning approaches, including gamification. However, in the context of CRE, gamification presents several challenges, such as shallow spiritual reflection, overreliance on extrinsic motivation, and potential digital distractions. Furthermore, limited studies have explicitly integrated gamification with theological reflection in Christian education. This study employs a qualitative approach using a literature review method, drawing from national and international journals, books, and relevant academic publications. Data were analyzed through data reduction, thematic categorization, and concept synthesis. The findings indicate that gamification has significant potential to enhance student motivation and engagement.